Bata, bata pa'no ka pinatay? a study on the portrayal of children and youth killed in Oplan Tokhang in select local online news outlets in Metro Manila from June 30, 2016 to September 15, 2017 - Dizon, Elijah Adnyc Jyle Gonzales; Gaspar, Maegan Camporedondo; Congjuico, Teresa S. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2017)
This research examines how select online news outlets in Metro Manila portray children and youth killed in Oplan Tokhang from June 30, 2016 to September 15, 2017. This study aims to: provide a profile of online news outlets' coverage of slain children and youth; determine the quality of coverage; and assess media practitioners' adherence to ethical guidelines on reporting set by the Department of Justice (DOJ), International Federation of Journalists (IFJ), Philippine Press Institute - National Press Club (PPI-NPC), the United Nations Children's Emergency Fund (UNICEF), and the Society of Professional Journalists (SPJ). This research was anchored on the Framing Theory of Media, Gate-keeping theory, and the ethical-decision making framework.

The researchers analyzed articles and accompanying photos and video six leading online news sites in Metro Manila namely Rappler.com, Interaksyon.com, Inquirer.net, GMA News Online, ABS-CBN News Online, and Philstar.com. Data were obtained through content analysis, interviews and research.

The findings of the study reveal that online news sites committed ethical transgressions in covering the cases of children killed in the anti-drug campaign amidst the existence of guidebooks furnished specially for reporting on children and youth.
Vita.
Keywords: Children in mass media .; Extrajudicial executions -- Philippines; Mass media -- Ethics